Providing Early Attending Physician Expertise via Telemedicine to Improve Rapid Response Team Evaluations*. Issue 5 (May 2020) - Fiero, Marie L.; Rosenblatt, Samuel; Zhang, Bingqing; Snyder, Megan; Priestley, Margaret A.; Chuo, John; Fuller, Kate; Mensinger, Janell; Bonafide, Christopher P.; Sutton, Robert M.
Abstract : Objectives: To evaluate the effect of providing early attending physician involvement via telemedicine to improve the decision process of rapid response teams. Design: Quasi-experimental; three pairs of control/intervention months: June/July; August/October; November/December. Setting: Single-center, urban, quaternary academic children's hospital with three-member rapid response team: critical care fellow or nurse practitioner, nurse, respiratory therapist. Baseline practice: rapid response team leader reviewed each evaluation with an ICU attending physician within 2 hours after return to ICU. Subjects: 1) Patients evaluated by rapid response team, 2) rapid response team members. Interventions: Implementation of a smartphone-based telemedicine platform to facilitate early co-assessment and disposition planning between the rapid response team at the patient's bedside and the attending in the ICU. Measurements and Main Results: As a marker of efficiency, the primary provider outcome was time the rapid response team spent per patient encounter outside the ICU prior to disposition determination. The primary patient outcome was percentage of patients requiring intubation or vasopressors within 60 minutes of ICU transfer. There were three pairs of intervention/removal months. In the first 2 pairs, the intervention was associated with the rapid response team spending less time on rapid response team calls (June/July: point estimate –5.24 min per call; p < 0.01; August/October: point estimate –3.34 min per call; p < 0.01). During the first of the three pairs, patients were significantly less likely to require intubation or vasopressors within 60 minutes of ICU transfer (adjusted odds ratio, 0.66; 95 CI, 0.51–0.84; p < 0.01). Conclusions: Early in the study, more rapid ICU attending involvement via telemedicine was associated with rapid response team providers spending less time outside the ICU, and among patients transferred to the ICU, a significant decrease in likelihood of patients requiring vasopressors or intubation within the first 60 minutes of transfer. These findings provide evidence that early ICU attending involvement via telemedicine can improve efficiency of rapid response team evaluations. Abstract : Supplemental Digital Content is available in the text.